Antioxidant potential of five compounds extract from the marine fungus Aspergillus flocculosus by DFR method: HAT and SET mechanism. - Trang, Phan Thi Thu; Van, Tran Thi Thanh; Chinh, Ngo Thi; Trinh, Phan Thi Hoai; Quang, Dao Duy (Vietnam Journal of Science and Technology, 2019)
Antioxidant potential of five compounds include ochraceopone F (1), aspertetranone D (2), cycloechinulin (3), wasabidienone E (4) and mactanamide (5) in the extracts from marine fungus Aspergillus flocculosus in Nha Trang was investigated by computational chemistry methods. All calculations were performed at the theoretical level M05-2X/6-311++G(d, p)//M05-2X/6-31+G(d) in the gas phase. The physicochemical properties such as bond dissociation energies (BDE), ionization energies (IE), electron affinity (EA) characterizing HAT (Hydrogen atom transfer) and SET (Single electronic transfer) antioxidant mechanisms were calculated. As a result, the H-atom donating ability of the studies compounds increases in the descending order of BDE value (1) > (2) > (3) > (4) » (5). Wherein the compounds (4) and (5) represent as the most potential antioxidant with the lowest BDE in the gas phase being 74.9 and 75.1 kcal/ mol. Moreover, the electronic donating ability of the compounds increases as function of the descending order of IE value (2) > (1) > (5) > (3) > (4). And the electron accepting abitlity decreases in decreasing EA value (4) > (3) > (2) > (5) > (1). Compound (4) (wasabidienone E) has the smallest IE value of 6.56 eV and has the largest EA value of 2.33 eV.